The correlation between sleep disorders and obesity – abnormal sleep duration as a risk factor for high weight - Radzka, Agnieszka; Mroczek, Anna; Fałkowska, Urszula; Pawlicka, Marta; Bałabuszek, Kamil; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2018)
Obesity and overweight are among the most common diseases in the world. Last data from 2016 showed that 650 million people were obese and since 1960 the number of obese people has increased three times, which is associated with "fast" lifestyle of the majority of the world’s population. This is the clue why so many scientists are looking for modified obesity factors. Overweight is a major risk factor for inter alia diabetes, cardiovascular diseases and cancers. Most studies have shown obesity as a cause of sleep disorders such as excessive daytime sleepiness EDS or sleep apnoea, but recent studies have suggested that sleep disorders cause obesity. Otyłość i nadwaga należą do najczęstszych chorób na świecie, ostatnie dane opublikowane w 2016r. wykazały, że 650 milionów osób było otyłych, a od 1960 r. liczba osób zmagających się z otyłością wzrosła trzykrotnie, co wiąże się z "szybkim" stylem życia większości populacji na świecie. W związku z tym, wielu naukowców szuka modyfikowanych czynników otyłości. Nadwaga jest głównym czynnikiem ryzyka między innymi cukrzycy, chorób sercowo-naczyniowych i nowotworów. Większość badań ukazuje otyłość, jako przyczynę zaburzeń snu, takich jak nadmierna senność EDS w ciągu dnia lub bezdech senny, ale ostatnie badania sugerują, że zaburzenia snu mogą powodować otyłość.